Macrosynteny analysis shows the absence of ancient whole-genome duplication in lepidopteran insects - Mc Lysaght, Aoife (My University, 2019)
Whole-genome duplication (WGD) is considered a key evolutionary event for genetic innovation and has occurred in diverse eukaryotic lineages (1). In PNAS, Li et al. (2) report multiple WGD events in hexapods, which is surprising because WGD is thought to be disruptive in animals with chromosomal sex determination and therefore expected to be rare (1). The argument by Li et al. (2) is based on gene-tree and molecular-clock analyses (except for a scaffold-level synteny analysis of the silkworm genome). However, gene-tree–based (or molecular-clock–based) approaches were previously shown to be potentially misleading (3, 4), whereas chromosome-scale macrosynteny-based approaches are more reliable and conclusive (5, 6). Here we examine the hypothesized Lepidoptera-specific genome duplication by macrosynteny analysis of the chromosome-level silkworm genome assembly (7). Contrary to the scaffold-scale synteny analysis performed by Li et al. (2), our chromosome-scale analysis shows the absence of WGD in silkworm and suggests that several large-scale genome duplications proposed by Li et al. may be artifactual.
PUBLISHED
Keywords: silkworm genome; Whole-genome duplication (WGD); diverse eukaryotic lineages; Genes & Society; COMPARATIVE GENOMICS; MOLECULAR EVOLUTION